The Problem of the Values Supporting Reasoning in the Humanities: Cognitive-Pragmatic Approach - Savtchouk, Tatiana (Respectus Philologicus, 2017)
The main cognitive models of the values supporting reasoning in the discourse of the humanities are identified, the typology of selected schemes is made, their modifications are characterised, the pragmatic differences of the models are determined. Particular attention is paid to the “cause to aim” justification of the value judgments that prevails in the humanities. The regularities of verbal representation of cognitive structures are ascertained, pragmatic properties of argumentative markers are explicated. The author’s typology of tactics that implements rational and emotional value-study strategies is proposed. A number of fallacies in the justification of normative value judgments are revealed, such as “semantic-pragmatic dissonance”, “simulation of reasoning”, “pseudoauthority”, “superfluity of argumentative resource”. The sources of such shortcomings are exemplified by the facts from the evidence base. The conclusion is that the author of the article chooses the cognitive model of argumentation in support of the values, the ways of its verbal presentation and the tactics of reasoning on the basis of pragmatic factors.